Molecular MRI of Liver Fibrosis by a Peptide Targeted Contrast Agent in an Experimental Mouse Model - Chow, April M. (2013)
Liver fibrosis is a common response to chronic liver injury that is associated with high morbidity and mortality. Clinical utility of conventional and advanced MRI techniques for staging liver fibrosis has yet to be established. Study on molecular MRI of liver fibrosis is limited mainly due to difficulty in searching for a specific biomarker and synthesizing corresponding molecular probe. Liver fibrosis is characterized by an increased amount of extracellular matrix consisting of fibril-forming collagens, and matrix glycoconjugates such as fibronectin, which may serve as a specific molecular target for contrast-enhanced molecular MRI. In this study, liver fibrosis was induced by carbon tetrachloride (CCl(4)) intoxication mimicking hepatic fibrosis and cirrhosis after 4 and 8 weeks. The feasibility of CGLIIQKNEC (CLT1) peptide-targeted nanoglobular contrast agent (Gd-P) for detection of liver fibrosis through molecular imaging of fibronectin was investigated at 7 T. Differential enhancements were observed and characterized between normal and fibrotic livers using Gd-P at 0.03 mmol/kg, comparing to non-targeted controls (Gd-CP and Gd-C). For Gd-P injection, both the peak and steady-state ΔR(1) of normal livers was significantly lower than those after 4-week and 8-week of CCl(4) dosing. Liver fibrogenesis with increased amount of fibronectin in the extracellular space in insulted livers were confirmed by histological observations. These results indicate that Gd-P binds to fibrin-fibronectin complexes in livers, demonstrating the possibility of staging and characterizing liver fibrosis by probing the accumulation of fibronectin in fibrotic livers with molecular MRI.